TEACHING QUANTUM PHYSICS BASED ON THE PRINCIPLE OF COHERENCE IN ACADEMIC LYCEUMS AND HIGHER EDUCATION INSTITUTIONS (Scientific journal of the Fergana State University, 2023)
The article analyzes the compatibility of studying the topic "black body irradiation" with the principle of continuity in the course of physics in universities, academic lyceums and General secondary educational institutions in the system of continuous education. The authors investigated the compatibility of the presentation of this topic in the educational literature (textbooks and manuals) with the principle of continuity, and also studied the deepening and enrichment of the content during the transition from one level to another